Development and Validation of a Simple and Sensitive ICP-MS Method for the Quantification of Elemental Impurities in Propafenone Hydrochloride Drug Substance - Raju, Chandrasekar; Jhanavi A, Subha; Sivagami , B.; Babu M., Niranjan (Jordan Journal of Pharmaceutical Sciences, 2023)
Elemental impurities are substances present in drug products, excipients, or drug formulations. They may be formed by the presence of catalysts and environmental contaminants. Elemental impurities can be detected by a sophisticated method such as Inductively Coupled Plasma Mass Spectrometry (ICP–MS). ICP-MS is an advanced method to detect elemental impurities in drug substances. In this study Propafenone hydrochloride drug was used, Propafenone Hydrochloride is an antiarrhythmic medication belonging to class 1C used to prevent supraventricular and ventricular arrhythmias. The present study was aimed to develop and validate inductively coupled plasma mass spectroscopic (ICP–MS) method for detection of elemental contaminants, i.e., Class 1, Cd, Pb, As, Class 2A, Hg, Co, V, and Class 2B impurities such as Ni, T1, Se, Ag, Au, Pd, Ir, Os, Rh, Ru, and Pt. Total 17 elemental impurities were detected in Propafenone Hydrochloride and this method was employed for the regular sample analysis of 17 elemental impurities in Propafenone Hydrochloride for pharmaceutical use. The instrument conditions were set using RF power of 1550 W, auxiliary gas of 0.5 L/min, and nebulizer flow of 1.01 L/min nebulizer pump pressure was 0.10 rps, spray chamber temperature was 2°C, and mode used was He, He flow rate was 4.3 mL/min and the energy discrimination rate was 3.0 V. The technique is sensitive and may identify desirable elemental impurities within permissible regulatory limits when additional elements are present. The proposed ICP-MS approach has been found to be accurate, precise, linear, rugged, robust, and convenient for the quality control of the drug substance propafenone hydrochloride. The linearity results for each impurity were 0.9990. The methods were validated according to USP requirements and International Council for Harmonization ICH guidelines. The suggested approach is an excellent quality control tool for the concurrent quantitative assessment and detection of elemental contaminants at low levels in the drug substance propafenone hydrochloride.